Retrospective analysis of cases consulted at the department of psychiatry in a general hospital in Guangzhou, China - Zhang LL; Zhao JP (Archive of Gerontology and Geriatrics Research - Peertechz Publications, 2021)
Objective: To comprehensively analyze cases of psychiatric consultation in a general hospital and provide a primary reference for the development of consultation-liaison psychiatry. Method: A retrospective study was conducted by analyzing data collected over a two-year period regarding psychiatric consultations from the inpatient registry in a general hospital.  Results: A total of 926 and 774 psychiatric consultations were recorded in 2016 and 2017, respectively. The most common reason for consultation was unexplained somatic symptoms. Consultations based on psychological evaluation, and mental/behavioral disorders due to organic diseases and perioperative stress were significantly higher in 2017 than those in 2016 (P<0.01). Diagnoses of neurotic, stress-related and somatoform disorders were significantly lower in 2017 compared to those in 2016 (269 [34.8%] cases in 2017 vs. 373 [40.3%] cases in 2016; P=0.019). Among specific diagnoses, generalized anxiety disorder was the most common. Conclusion: Most patients with depressive or anxiety disorders visit a general hospital due to somatic symptoms. It is necessary to train non-psychiatrists to identify mental disorders efficiently, as well as to extend the comprehensive consultation model to include more clinical departments.